Performance of Weaned Rabbits Raised in Cages or Pens in Northern Guinea Savannah Zone of Nigeria - Shehu, B M; Mahmoud, M M (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2013)
Abstract. Management system in rabbit production has been reported to affect the performance of rabbits. In view of this, an eight week study was conducted to evaluate the effects of two different management systems (cage-housed and pen-housed) on the growth performance indices of weaned rabbits in Northern Guinea Savannah zone of Nigeria. Twenty four (24) weaned rabbits of heterogeneous breeds in equal sexes, aged between 5-6 weeks, with live weight of 612±14.72 g were used for the study. The rabbits were randomly divided into two groups (cage-housed and pen-housed) consisting of 12 rabbits per group. They were fed commercial diet (concentrate) supplemented with Tridax procumbens and given access to clean fresh water adlibitum. The experiment lasted for 8 weeks. Results from the study showed a significant difference (P<0.05) in daily body weight gain, feed intake and final body weight. Caged-housed Rabbits recorded higher daily weight gain, daily feed intake 72.24±0.07 g/day and final body weight of 1373±41.57 g as against 9.92±0.38 g/day, 63.58±0.88 g/day and 1168±23.36 g, respectively for the pen-housed rabbits. It is concluded that rabbits raised in cages had better growth performance indices than those raised in pens. It is however, recommended that further studies be conducted to assess the welfare of rabbits raised under the two management systems. Key words: Growth performance, weaned rabbits, management systems. Abstrak. Sistem pemeliharaan ternak kelinci mempengaruhi performan kelinci. Penelitian telah dilakukan selama 8 minggu untuk mengevaluasi pengaruh dua sistem pemeliharan yang berbeda terhadap index pertumbuhan kelinci lepas sapih di area Northern Guinea Savannah, Nigeria. Dua puluh empat (24) kelinci lepas sapih dengan jenis kelamin sama, umur 5-6 minggu dengan bobot hidup 612±14,72 g digunakan dalam penelitian ini. Kelinci dibagi secara acak ke dalam dua kelompok (kandang terkurung dan pen), setiap kelompok 12 kelinci. Kelinci diberi pakan konsentrat disuplementasi dengan Tridax procumbens dan air diberikan secara adlibitum. Eksperimen berlangsung selama 8 minggu. Hasil penelitian menunjukkan perbedaan nyata pada kenaikan bobot harian, asupan pakan dan bobot akhir. Kelinci yang dikandang terkurung memiliki pertambahan bobot badan harian 13,62±0,70 g/hari, asupan pakan harian 72,24±0,07 g/hari, dan bobot badan akhir 1373±41,57 g yang lebih tinggi daripada kelinci dalam kandang pen, secara berturut-turut yaitu 9,92±0,38 g/hari, 63,58±0,88 g/hari dan 1168±23,36 g. Disimpulkan bahwa kelinci yang dipelihara dalam kandang terkurung memiliki indeks pertumbuhan yang lebih baik daripada yang di dalam pen. Penelitian lebih lanjut disarankan guna mengukur kenyamanan kelinci yang dipelihara dengan dua sistem pemeliharaan tersebut. Kata kunci: Performan pertumbuhan, kelinci lepas sapih, sistem pemeliharaan